Estudo gravimétrico na delimitação do arcabouço geológico – estrutural do depósito polimétalico Santa Maria - RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The Camaquã Mine region has historically been known to have mineralization in several mining cycles since the late nineteenth century. Structural geological characterization is usually carried out on the surface with a lack of subsurface data. These are usually carried out by means of exploratory phase surveys which, however, are costly and require time for analysis, description and final characterization. The application of geophysics is an indirect and non-invasive approach. In addition, it provides subsidies on structures, density variations and lithological contacts on both surface and deep levels. The present is about terrestrial gravimetric acquisition of detail in an area located southwest of the Camaquã Sedimentary Basin. The site is represented by sedimentary and volcanic sedimentary lithologies, and there is also volcanism and associated plutonism. It was possible to interpret the data and characterize the gravimetric geophysical signature of the rocks and discontinuities (faults, fractures and intrusive bodies) from the geophysical and lithological profiles by sectioning the main structures and lithologies. The analysis of the gravimetric data also offers the recognition and interpretation of the lithologies from the integration to the data of probe testimony allowing the calibration and emphasizing the reliability of the gravimetric processing
Keywords: Bacia do Camaquã; Gravimetria; Técnicas de processamento; Camaquã Basin; Gravimetry; Processing techniques; CNPQ::CIENCIAS EXATAS E DA TERRA